ANALISIS PENDAPATAN USAHA TAMBAK UDANG VANNAMEI DI DESA BOYANTONGO KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Nurhasni, Nurhasni; Antara, Made; Laapo, Alimudin (AGROTEKBIS, 2019)
This research aims to identify the income of Vennamei shrimp fishpond business in Boyatongo Village South Parigi Sub-district, Parigi Moutong Regency. This research was conducted on May to July 2017 in Boyatongo Village South Parigi Sub-district, Parigi Moutong Regency. The location of the research was selected by purposively  through consideration that this village is one of area that produce Vennamei shrimp with extensive harvested area and high production in Parigi Moutong. Sample of respondent was determined through census. Sample taken was all community who cultivate the Vennamei shrimp. The total number of respondent were 12 people of Vennamei shrimp farmers. Analysis used was income analysis. The result of analysis showed that the average production I is 372.5 kg/3ha or 124.1 kg/ha with selling price of Rp. 45.000/ kg, the average production of II is 85 kg/3 ha or 28 kg/ha and the selling price is Rp. 40.000/kg. The average of income earn by the farmer is Rp. 20.179.167/3ha or Rp. 6.726.389/ha. The permanent cost is Rp. 2.922.428/3ha or Rp. 974.143/ha and the average of variable cost is Rp. 7.679.833/3ha or Rp. 2.559.944/ha. The average of outcome is Rp. 10.602.262/3ha or Rp. 3.534.087/ha. Therefore, the average income of farmer is Rp. 9.576.905/3ha or Rp. 3.192.302/ha.